2010
DOI: 10.4196/kjpp.2010.14.5.337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Serotonin on the Induction of Long-term Depression in the Rat Visual Cortex

Abstract: Long-term potentiation (LTP) and long-term depression (LTD) have both been studied as mechanisms of ocular dominance plasticity in the rat visual cortex. In a previous study, we suggested that a developmental increase in serotonin [5-hydroxytryptamine (5-HT)] might be involved in the decline of LTP, since 5-HT inhibited its induction. In the present study, to further understand the role of 5-HT in a developmental decrease in plasticity, we investigated the effect of 5-HT on the induction of LTD in the pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…Since the relative strength of inhibition compared with excitation is more important than the development itself [28], we investigated the development of phasic inhibition relative to the same amount of excitation in different age groups. We found a developmental increase in the inhibitory-to-excitatory ratio (I/E ratio), which confirmed our previous findings [11]. Inhibition increased during post-natal development from 3 to 8 weeks and reached a plateau at 8 weeks of age.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Since the relative strength of inhibition compared with excitation is more important than the development itself [28], we investigated the development of phasic inhibition relative to the same amount of excitation in different age groups. We found a developmental increase in the inhibitory-to-excitatory ratio (I/E ratio), which confirmed our previous findings [11]. Inhibition increased during post-natal development from 3 to 8 weeks and reached a plateau at 8 weeks of age.…”
Section: Discussionsupporting
confidence: 78%
“…In a previous study, we reported the development of synaptically evoked phasic inhibition during the critical period from 3 to 5 weeks of age in the rat visual cortex [11]. To further evaluate the development of inhibition, in the present study we extended the time period to 12 weeks of age.…”
Section: Development Of Phasic Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the visual cortex, 5-HT regulates the development of phasic inhibition (Jang et al, 2010), and the induction of long-term synaptic plasticity (Kim et al, 2006;Moreau et al, 2013) and ocular dominance (OD) plasticity (Gu and Singer, 1995 Since GABAergic inhibition is also critically involved in the regulation of long-term synaptic plasticity (Jang et al, 2009) and OD plasticity (Hensch et al, 1998), 5-HT signaling on GABAergic inhibition has been of particular interest. Although we previously reported that 5-HT enhances phasic inhibition (Jang et al, 2012), it is largely unknown whether 5-HT affects tonic inhibition in the visual cortex and in other brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…In the visual cortex, the expression of 5-HT receptor subtypes also changes during postnatal development in cats (Kojic et al 2000) and rats (Li et al 2004), which implies that 5-HT may exert different functions during the lifespan. For example, whereas 5-HT facilitated the induction of long-term potentiation (LTP) in the visual cortex of adult rats (Vetencourt et al 2008), it was also involved in the age-dependent decline of N-methyl-D-aspartate (NMDA) receptor-dependent LTP (Edagawa et al 2001;Kim et al 2006) and long-term depression (LTD) (Jang et al 2010) during the critical period (postnatal 3-5 wk in rat visual cortex).…”
mentioning
confidence: 99%